2021
DOI: 10.16899/jcm.911185
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Factors Impacting Length of Hospital Stay of COVID-19 Inpatients

Abstract: Knowing the typical length of hospital stay of COVID-19 patientsand which factors affecting the stay time are important for hospital management.A factor can impact the stay time in conflicting ways: a condition may,by the same mechanism, increase the stay time for a severe patient while decrease the time for an even more severe and deceased patient.Material and Method: 3184 COVID-19 patients from the Tokat State Hospital were examined on arrival to determine if they are required further treatment in hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
(47 reference statements)
6
12
0
3
Order By: Relevance
“…The short-term glucose has been shown to be a much stronger predictor for COVID-19 severity than the history of diabetes status (Singh and Singh, 2020; Coppelli et al, 2020; Ling et al, 2021; Cetin et al, 2021d; Guarisco et al, 2022). In a recent study, it was shown that higher glucose level ( > 180) had increased the odds of death by 4-fold for non-diabetes, whereas only 1.8-fold increase for diabetes COVID-19 patients (Skwiersky et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The short-term glucose has been shown to be a much stronger predictor for COVID-19 severity than the history of diabetes status (Singh and Singh, 2020; Coppelli et al, 2020; Ling et al, 2021; Cetin et al, 2021d; Guarisco et al, 2022). In a recent study, it was shown that higher glucose level ( > 180) had increased the odds of death by 4-fold for non-diabetes, whereas only 1.8-fold increase for diabetes COVID-19 patients (Skwiersky et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… Elevated ferritin serum levels have been found to significantly correlate with COVID-19 severity, as discussed in these papers ( Lin et al, 2020 , Carubbi et al, 2021 , Ahmed et al, 2021 , Kaushal et al, 2022 , among others. The short-term glucose has been shown to be a much stronger predictor for COVID-19 severity than the history of diabetes status ( Singh and Singh, 2020 , Coppelli et al, 2020 , Ling et al, 2020 , Cetin et al, 2021d , Guarisco et al, 2022 . In a recent study, it was shown that higher glucose level (> 180) had increased the odds of death by 4-fold for non-diabetes, whereas only 1.8-fold increase for diabetes COVID-19 patients ( Skwiersky et al, 2021) .…”
Section: Discussionmentioning
confidence: 99%
“…The short-term glucose has been shown to be a much stronger predictor for COVID-19 severity than the history of diabetes status ( Singh and Singh, 2020 , Coppelli et al, 2020 , Ling et al, 2020 , Cetin et al, 2021d , Guarisco et al, 2022 . In a recent study, it was shown that higher glucose level (> 180) had increased the odds of death by 4-fold for non-diabetes, whereas only 1.8-fold increase for diabetes COVID-19 patients ( Skwiersky et al, 2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Yaşam analizinde, yaşam süresini etkileyecek değişkenleri belirlemek için Cox orantılı hazard modelinin kullanılabilmesi için değişkenlerin orantılı hazard varsayımını sağlaması gerekmektedir. Orantılı hazard varsayımının test edilmesinde; log(-log) yaşam eğrileri, gözlenen ve beklenen yaşam eğrileri, Schoenfeld artıkları ile yaşam süresinin rankı arasındaki korelasyon testi yöntemi ve modele zamana bağlı açıklayıcı değişkenlerin eklenmesi yöntemleridir [8,15,16].…”
Section: Materyal Ve Metotunclassified
“…Çetin vd. 'leri Tokat devlet hastanesinde yatılı olarak tedavi gören 404 hastanın; yaş, cinsiyet, yoğun bakımda tedavi olma durumu ile bazı klinik faktörlerin yatılı olarak kalma süresi üzerindeki etkisini doğrusal regresyon ve Cox-regresyon modelleri ile ortaya koymuşlardır [8].…”
unclassified